Tingkat Kepuasan terhadap Konseling Apoteker tentang Penyakit Degeneratif di Lapangan Sempur, Kota Bogor - Sa'adah, Aas; Dian Farida Ismyama; Honifa, Honifa; Koniah, Eni (Jurnal Kesehatan Komunitas, 2024)
The number of individuals experiencing degenerative diseases is increasing from year to year, making it a burden on the government. Currently, counseling by pharmacists is very rarely carried out so the role of pharmacists is not optimal for prevention and early identification of degenerative diseases. This research aims to determine the level of community satisfaction with pharmacist counseling in Sempur Field, Bogor. Research method using cross-sectional. The sample amounted to 100 respondents, taken using an accidental sampling technique. Data was collected through a questionnaire from September to November 2023. Counseling satisfaction is measured using a Likert scale, namely sequentially from the first question item to the ninth. Analyzed descriptively observationally in the form of frequencies and percentages. The results of this research obtained the characteristics of respondents, age, gender, education, occupation, and ethnicity,  aged 17 - 25 and 45 - 55 years 38%, 49%, 74% women, 51% high school were housewives and Sundanese of respondents' knowledge degenerative disease were 57% poor, and 43% good and the results obtained from the level of satisfaction with counseling carried out by pharmacists showed that the level of patient satisfaction reached 88.75%, falling into the high satisfaction category. Aspects assessed include the way the pharmacist discusses and conveys information, the pharmacist's questions regarding the history of degenerative diseases, confidentiality, the respondent's knowledge, Response from the pharmacist, the language used, duration of counseling time, the way the pharmacist interacts, and the information conveyed by the pharmacist.